Using pLink to Analyze Cross‐Linked Peptides. Issue 1 (15th February 2018) - Fan, Sheng‐Bo; Meng, Jia‐Ming; Lu, Shan; Zhang, Kun; Yang, Hao; Chi, Hao; Sun, Rui‐Xiang; Dong, Meng‐Qiu; He, Si‐Min
Abstract: pLink is a search engine for high‐throughput identification of cross‐linked peptides from their tandem mass spectra, which is the data‐analysis step in chemical cross‐linking of proteins coupled with mass spectrometry analysis. pLink has accumulated more than 200 registered users from all over the world since its first release in 2012. After 2 years of continual development, a new version of pLink has been released, which is at least 40 times faster, more versatile, and more user‐friendly. Also, the function of the new pLink has been expanded to identifying endogenous protein cross‐linking sites such as disulfide bonds and SUMO (Small Ubiquitin‐like MOdifier) modification sites. Integrated into the new version are two accessory tools: pLabel, to annotate spectra of cross‐linked peptides for visual inspection and publication, and pConfig, to assist users in setting up search parameters. Here, we provide detailed guidance on running a database search for identification of protein cross‐links using the 2014 version of pLink. © 2015 by John Wiley & Sons, Inc.